Effect of 2 MeV W+ ion irradiation on the surface morphology of Sc:In:C and Zr:In:C thin films. Issue 11 (2nd December 2021) - Cannavò, A.; Vacik, J.; Lavrentiev, V.; Ceccio, G.; Horak, P.; Vasi, S.; Bakardjieva, S.
Abstract : In this work, a comparative study of surface morphology and elemental distribution of thin films of the M:In:C (with M = Sc or Zr) ternary composites irradiated with 2 MeV W + ions with fluences 10 14  cm − 2 and 10 15  cm − 2 was carried out. The films were prepared by ion beam sputtering of the M, In and C targets followed by thermal annealing in a high vacuum. The surface morphology was monitored by Atomic Force Microscopy (AFM), and the elemental composition by Rutherford Backscattering Spectroscopy (RBS) in the regime of elastic scattering (2000 keV He +  ions energy) and nuclear resonant scattering (3046 and 4280 keV He + ions for O and C resonances, respectively). It has been shown that both deployed modifications (thermal annealing and ion beam irradiation) seriously affect the surface morphology and the elemental distribution of both composites. It turned out that the main reason for the changes is a decrease in the content of indium in the composites, which after irradiation with a high fluence of 10 15  cm − 2 decreased to almost zero. It also turned out that the morphological changes take place differently in the inspected composites - more significantly in Zr:In:C, less in Sc:In:C.